Technological breakthroughs impact within the cultural communicative process in regard to social media (2016)
Technological advances represent a fundamental change in the new millennium; besides, these advances has generated a great development in everything that daily works inside the world. One key change is based on the way people communicate by using technology tools; the increasingly common use puts the communication model in constant changing starting to separate each variable as a unit. At the same time intercultural, interaction and adaptation play an important role in the communication process by the use of technological advances; consequently these factors lead to increased effectiveness in measuring the success of communication.